The effect of environmental pressure changes on the retentive strength of cements for orthodontic bands - Gulve, Meenal N; Gulve, Nitin D; Shinde, Renu; Kolhe, Swapnil J (Diving and hyperbaric medicine, 2012)
The purpose of this study was to evaluate the effect of environmental pressure changes on the retentive strength of orthodontic bands cemented with conventional glass ionomer cement or resin-modified glass ionomer cement. Stainless steel bands were cemented to 80 extracted first and second molars in two equal groups comprising conventional glass ionomer cement and resin-modified glass ionomer cement. Each group was randomly divided into two sub-groups of 20 samples each, one sub-group to act as a control, and the other to be used experimentally. After seven days of storage, the experimental groups were subjected to simulated dives to 405 kPa [corrected] for 3 minutes, 15 times in a pressure pot, after which the force required to deband was tested using a universal testing machine. The data were statistically analysed using Student's t-tests, significance being assumed at P < 0.001. The retentive strength of bands cemented with conventional glass ionomer in the pressure-cycled group was statistically significantly less than that in the control group. No statistically significant difference in strength was found between the two groups cemented with resin-modified glass ionomer. This study showed that the retentive strength of bands cemented with conventional glass ionomer is reduced after pressure cycling. We suggest that dentists should consider using resin-modified glass ionomer cement for cementing orthodontic bands for patients who are divers and thus likely to be exposed to raised-pressure cycling.